Curriculum Development For Children With Adhd Reviewed From Learning Innovation - Ledyari Noviyanti, Putu; Suharta, I Gusti Putu; Lasmawan, I Wayan (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurobehavioral disorder that commonly occurs in children who often have difficulty paying attention, controlling impulses, and having a high level of activity. Curricula designed specifically for children with ADHD aim to maximize their potential, while accommodating the challenges they face in information processing, attention regulation, and self-regulation. The aim of this research is to provide an overview of curriculum developments for children with ADHD in terms of innovations in learning using research methods, namely literature reviews and research results in the form of various curriculum developments for children with ADHD, especially in the form of innovations in inclusive learning in the application of kinesthetic learning styles, application of models. Project Based Learning and CTL learning with the help of Self Instruction and innovative learning aids in the form of playdough, Montessori teaching aids and play equipment with QR codes.